2018
DOI: 10.5194/acp-18-1291-2018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (2001–2012) trends of carbonaceous aerosols from a remote island in the western North Pacific: an outflow region of Asian pollutants

Abstract: Abstract. The present study reports on long-term trends of carbonaceous aerosols in total suspended particulate (TSP) samples collected at Chichijima in the western North Pacific during [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012]. Seasonal variations of elemental carbon (EC), organic carbon (OC), and water-soluble organic carbon (WSOC) concentrations showed maxima in winter to spring and minima in summer. These seasonal differences in the concentrations of carbonaceous aerosols wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 114 publications
(108 reference statements)
0
37
0
Order By: Relevance
“…Anthropogenic SOA precursor emissions consist of ~40% alkanes, ~10% alkenes, and ~20% aromatics (mostly trimethylbenzenes, xylenes and toluene), the remaining part being oxygenated and unidentified compounds [11]. Most of the anthropogenic SOA is formed from the oxidation of substituted monoaromatic compounds and long-chain alkenes [31,51] emitted from sources such as fossil fuel burning, vehicle emissions, biomass burning, solvent use and evaporation [52][53][54][55][56][57][58][59][60]. Global emission of aromatic compounds is about 18.8 Tg year −1 [61] and results in an estimated range of SOA production of 2-12 Tg year −1 [61].…”
Section: Major Sources Of Soa Precursors: Current Knowledge From Emismentioning
confidence: 99%
“…Anthropogenic SOA precursor emissions consist of ~40% alkanes, ~10% alkenes, and ~20% aromatics (mostly trimethylbenzenes, xylenes and toluene), the remaining part being oxygenated and unidentified compounds [11]. Most of the anthropogenic SOA is formed from the oxidation of substituted monoaromatic compounds and long-chain alkenes [31,51] emitted from sources such as fossil fuel burning, vehicle emissions, biomass burning, solvent use and evaporation [52][53][54][55][56][57][58][59][60]. Global emission of aromatic compounds is about 18.8 Tg year −1 [61] and results in an estimated range of SOA production of 2-12 Tg year −1 [61].…”
Section: Major Sources Of Soa Precursors: Current Knowledge From Emismentioning
confidence: 99%
“…The WSOC/OC ratios exceeding 0.4 indicate the aged aerosols with the significant contribution of SOA (Boreddy et al, 2018). The average WSOC/OC ratio of 0.64 in the present study indicates that OAs in Nanjing were relatively aged.…”
Section: Carbonaceous Componentsmentioning
confidence: 44%
“…Organic carbon (OC) and elemental carbon (EC) were measured using a Sunset Laboratory carbon analyzer following the IMPROVE (Interagency Monitoring of Protected Visual Environments) thermal-optical evolution protocol and assuming carbonate carbon to be insignificant in the sample (Boreddy et al, 2018). An area of 1.54 cm 2 of each quartz filter sample was insert in a quartz boat inside the thermal desorption chamber of the analyzer, and then stepwise heating was performed.…”
Section: Carbonaceous Components Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…7b). Similarly, Boreddy et al (2018) found no correlation between sea-salt and WIOC in the western North Pacific.…”
Section: Relationships Of Wioc and Wsoc With Na + Over The Southern Omentioning
confidence: 90%